Pneumonitis after immune checkpoint inhibitor therapies in patients with acute myeloid leukemia: A retrospective cohort study. Issue 14 (22nd April 2022) - Sheshadri, Ajay; Goizueta, Alberto A.; Shannon, Vickie R.; London, David; Garcia‐Manero, Guillermo; Kantarjian, Hagop M.; Ravandi‐Kashani, Farhad; Kadia, Tapan M.; Konopleva, Marina Y.; DiNardo, Courtney D.; Pierce, Sherry; Zarifa, Abdulrazzak; et al.
Abstract : Background: Immune checkpoint inhibitors (ICI), combined with hypomethylating agents, can be used to treat acute myeloid leukemia (AML), but this strategy results in a high rate of pneumonitis. The authors sought to determine risk factors for pneumonitis development and whether pneumonitis increased mortality. Methods: The authors conducted a retrospective review of 258 AML patients who received ICI‐containing regimens from 2016 to 2018. A multidisciplinary adjudication committee diagnosed pneumonia and pneumonitis by reviewing symptoms, imaging, microbiology, and response to therapies. To measure risk factors for pneumonitis and mortality, multivariate Cox proportional hazards models were constructed. Pneumonia, pneumonitis, and disease progression were modeled as a time‐dependent variable and incorporated a standard risk set modifying variables into the models. Results: Thirty patients developed pneumonitis (12%). Of these, 17 had partial or complete resolution, whereas 13 patients died from pneumonitis. Increasing age (hazard ratio [HR], 1.04 per year; 95% confidence interval [CI], 1.00‐1.08), and baseline shortness of breath increased pneumonitis risk (HR, 2.51; 95% CI, 1.13‐5.55). Female sex (HR, 0.33; 95% CI, 0.15‐0.70) and increasing platelet count (HR, 0.52 per log‐unit increase; 95% CI, 0.30‐0.92) decreased pneumonitis risk. In adjusted models, ICI‐related pneumonitis significantly increased mortality (HR, 2.84; 95% CI, 1.84‐4.37). Conclusions: ICI‐related pneumonitis occurs at a high rate in AML patients and increases mortality. Lay Summary: Immune checkpoint inhibitors (ICIs) remove inhibitory signals that reduce T‐cell function and allow T‐cells to better attack cancer cells. In acute myeloid leukemia (AML), the effectiveness of ICIs is limited in part by inflammation of the lung, called pneumonitis. This study reviewed 258 patients with AML who received ICIs and identified 30 patients who developed pneumonitis, nearly half of whom died. Older age and baseline shortness of breath increased pneumonitis risk, whereas female sex and higher baseline platelet counts decreased pneumonitis risk. Pneumonitis increased mortality by nearly 3‐fold. This work highlights the significant harm imposed by pneumonitis after ICI therapies. Abstract : Pneumonitis occurs in 12% of patients with acute myeloid leukemia undergoing immune checkpoint inhibitor therapy and increases mortality by nearly 3‐fold.